Efektivitas latihan kepemimpinan Pancasila online bagi mahasiswa baru jurusan Hukum dan Kewarganegaraan Universitas Negeri Malang - Wulandari Wulandari; Margono Margono; Sudirman Sudirman (Universitas Negeri Malang, 2021)
This research aims to describe the purpose, implementation and effectiveness of the online Pancasila leadership training for new students majoring in HKn in the midst of the Covid-19 pandemic. This research uses a qualitative approach with a descriptive qualitative type. Data collection techniques using observation, interviews, and documentation. The results showed that there were four main objectives, namely (a) introducing new students to the HKn department to be more interested and proud, (b) making new students enthusiastic about getting to know the world of lectures through habituating academic culture even in the midst of a pandemic, (c) forming character values. The value of Pancasila and applying it in college life, (d) fostering a sense of solidarity among new students majoring in Hkn, the implementation of online LKP was held for two days on 24 and 25 October 2020 in the Doctoral Workroom A9.109 FIS and in the department's laboratory through the application Zoom. The committee and lecturers provide material in the room that has been provided and the LKP participants take part in a series of activities from their respective homes using laptops. Online LKP has been quite effective in being implemented in the midst of a pandemic. Penelitian ini bertujuan untuk Mendiskripsikan tujuan, pelaksanaan dan efektivitas Latihan kepemimpinan Pancasila online bagi mahasiswa baru jurusan HKn di tengah pandemi covid-19. Penelitian ini menggunakan pendekatan kualitatif dengan jenis kualitatif deskriptif. Teknik pengumpulan data menggunakan observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukan bahwa terdapat empat tujuan utama yaitu (a) mengenalkan mahasiswa baru terhadap jurusan HKn agar lebih tertarik dan bangga, (b) menjadikan mahasiswa baru semangat dalam mengenal dunia perkuliahan melalui pembiasaan kultur akademik meski di tengah pandemi, (c) membentuk karakter nilai-nilai Pancasila dan menerapkan dalam kehidupan perguruan tinggi, (d) menumbuhkan rasa solidaritas antar mahasiswa baru jurusan Hkn, pelaksanaan LKP online dilaksanakan selama dua hari pada tanggal 24 dan 25 Oktober 2020 di ruang Kerja Doktor A9.109 FIS dan di laboratorium jurusan melalui aplikasi Zoom. Panitia dan dosen memberikan materi di ruangan yang telah disediakan tersebut dan peserta LKP mengikuti rangkaian kegiatan dari rumah masing-masing menggunakan laptop. LKP online sudah cukup efektif dilaksanakan di tengah pandemi.